Perancangan Distribusi Hasil Produk Textil dengan Rute Terdekat dengan Algoritma Greedy - Wibowo, Alvin Cahyo; Wowor, Alz Danny (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Delivery is one of the keys to a business because if there is no delivery, the work or flow of a business will be disrupted. The textile industry is one of many industries that really need delivery services with the closest route in order to save time. Greedy algorithm is an algorithm that is heuristic and its logical sequence is arranged based on problem solving steps that are arranged systematically. This study aims to design the distribution of textile products with the closest route using the Greedy Algorithm with a case study of CV. Karya Cahaya Lestari with the benefit of speeding up delivery times and helping drivers to save travel time. The final result of designing the distribution of textile products is in the form of a graph, specifically the Directed Graph, a map like the one in the picture basically only shows interconnected points, with a certain distance at each point..